Environment-friendly aerogel and preparation method thereof
By using degradable materials such as pea starch and polyvinyl alcohol, and adding concave and concave rock stone and flame retardant stabilizer, the problem of environmental pollution in traditional aerogels is solved, and the high flame retardancy and mechanical properties of environmentally friendly aerogels are achieved.
Patent Information
- Application Number
- CN202411885835.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-04
AI Technical Summary
The organic polymers used in the preparation of traditional aerogels are difficult to obtain and difficult to decompose, resulting in environmental pollution.
Pea starch and polyvinyl alcohol are used as the main raw materials, and cross-linked by pentadialdehyde to form an environmentally friendly aerogel with a three-dimensional network structure, and add concave and concave rock stone and flame retardant stabilizer to the aerogel to improve flame retardant and mechanical properties.
The good environmental protection, flame retardant properties and mechanical properties of the aerogel are achieved. The aerogel is easily degraded after being discarded, reducing environmental pollution.
Smart Images

Figure BDA0005199262740000071 
Figure BDA0005199262740000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aerogels, and in particular to an environmentally friendly aerogel and a preparation method thereof. Background Art
[0002] Aerogel plays an important role in thermal insulation materials, aerospace, pharmaceuticals and medicine due to its good thermal insulation properties, low density and high porosity.
[0003] However, traditional aerogels, such as all-carbon aerogels, require organic polymers as raw materials in the preparation process. Organic polymers are often derived from petroleum resources and are difficult to obtain. In addition, due to their unique structure and chemical bonds, organic polymers are difficult to decompose in the natural environment, resulting in a large amount of waste existing in the environment for a long time, causing serious environmental pollution. Summary of the invention
[0004] In order to reduce the pollution to the environment, the present application provides an environmentally friendly aerogel and a preparation method thereof.
[0005] In the first aspect, the present application provides an environmentally friendly aerogel, which adopts the following technical solution: An environmentally friendly aerogel comprises the following raw materials in parts by weight: 100-120 parts of pea starch, 22-28 parts of polyvinyl alcohol and 2-4 parts of glutaraldehyde.
[0006] By adopting the above technical solution, the aerogel prepared by using pea starch and polyvinyl alcohol not only has good environmental protection, but also has excellent flame retardant and mechanical properties. The specific reasons are analyzed as follows: First of all, pea starch is renewable and biodegradable, and polyvinyl alcohol is water-soluble, biocompatible and biodegradable. Therefore, the aerogel prepared with pea starch and polyvinyl alcohol as the main raw materials has good environmental protection. When the aerogel is discarded, it is easy to degrade in the natural environment, thereby reducing the pollution to the environment.
[0007] In addition, pea starch can form a three-dimensional network structure, and pea starch and polyvinyl alcohol react to form hydrogen bonds, which increases the cross-linking density, thereby enhancing the density of the network structure, and further improving the flame retardant and mechanical properties of the aerogel.
[0008] Pea starch molecular chains contain a large number of hydroxyl groups, so they can be cross-linked with glutaraldehyde, further enhancing the density of the network structure.
[0009] In addition, pea starch has good charring properties. When burned, it releases carbon dioxide and carbon monoxide and forms a carbon layer, which inhibits the spread of heat and oxygen, thereby achieving a better flame retardant effect.
[0010] Preferably, the raw material further comprises 7-9 parts of a flame retardant, and the flame retardant comprises attapulgite.
[0011] By adopting the above technical solution, since polyvinyl alcohol is flammable, the flame retardant property of aerogel can be improved by adding a flame retardant.
[0012] Under high temperature, the volatilization of water in the internal structure of attapulgite can effectively slow down the combustion reaction; at the same time, a large amount of magnesium and aluminum elements inside form a stable oxide layer at high temperature, thereby hindering the spread of flames and the transfer of heat, and achieving a good flame retardant effect.
[0013] In addition, attapulgite is a fibrous structure. On the one hand, it can better support the carbon layer after the polymer is burned and carbonized, further improving the flame retardant effect. On the other hand, the fibrous structure gives attapulgite an excellent aspect ratio. Therefore, when attapulgite is wrapped in aerogel, it can form a more solid and dense skeleton structure, further improving the mechanical properties of the aerogel.
[0014] Preferably, the flame retardant further comprises a flame retardant stabilizer; The preparation method of the flame retardant stabilizer comprises the following steps: The shell powder is added to deionized water, stirred evenly to obtain a shell powder suspension, phytic acid is added, the upper suspension is collected by filtering after standing, the suspension is centrifuged and the lower precipitate is collected, and the precipitate is freeze-dried to obtain a flame retardant stabilizer; The method for preparing the flame retardant comprises the following steps: The attapulgite and the flame retardant stabilizer are mixed and stirred evenly to prepare the flame retardant.
[0015] By adopting the above technical scheme, phytic acid can form a flame retardant stabilizer with shell powder. Since phytic acid contains a large amount of phosphorus element, the flame retardant stabilizer generates a non-volatile phosphide layer during the combustion process, while reducing the concentration of combustible gas in the gas phase, thereby slowing down the combustion reaction rate.
[0016] Therefore, by forming a flame retardant stabilizer through phytic acid and shell powder, and then adding the flame retardant formed by the flame retardant stabilizer and attapulgite into the aerogel, on the one hand, it has a positive effect on improving the flame retardancy of the aerogel, and on the other hand, it can reduce the phenomenon that the aerogel is deformed and easily brittle and broken due to the addition of too much attapulgite.
[0017] Preferably, the mass ratio of the attapulgite to the flame retardant stabilizer is (3-5):1.
[0018] By adopting the above technical solution and controlling the mass ratio of attapulgite to the flame retardant stabilizer within the above range, the flame retardant properties and mechanical properties of the aerogel can be effectively improved.
[0019] Preferably, the raw materials also include 1-3 parts of chitosan.
[0020] By adopting the above technical solution, on the one hand, glutaraldehyde can react with chitosan to strengthen the chemical cross-linking effect between them, thereby having a positive effect on improving the density.
[0021] In addition, chitosan can produce nitrogen during thermal degradation to dilute the oxygen in the air in the combustion area, thereby hindering the combustion reaction and improving the flame retardant properties of aerogel.
[0022] In addition, chitosan is combined with flame retardant stabilizer to form a hard and dense complex layer, which can not only effectively hinder the transfer of heat to the inside and better protect the inside of the aerogel; but also improve the density of the aerogel surface, so that the mechanical properties of the aerogel are further improved.
[0023] Preferably, the raw material also includes 3-5 parts of boric acid.
[0024] By adopting the above technical solution, boric acid forms covalent crosslinks with pea starch and polyvinyl alcohol in an aqueous solution, so that the aerogel forms a multi-crosslinked network structure, thereby further improving the flame retardant properties and mechanical properties of the aerogel.
[0025] In addition, boric acid can form a dense protective film with phytic acid on the surface of aerogel, thereby reducing the contact between aerogel and oxygen in the air and improving the flame retardant effect of aerogel.
[0026] Preferably, the pea starch is prepared by modification, and the modification preparation method of the pea starch comprises the following steps: Pea starch is added to ethyl acetate and stirred evenly to obtain a starch suspension, and then pyridine is added and stirred evenly. Acryloyl chloride is added and stirred sufficiently. After the reaction at room temperature, excess ethanol is added to terminate the reaction. The reaction is then allowed to stand, washed and dried in sequence to obtain a modified starch.
[0027] By adopting the above technical scheme, pea starch is esterified with ethyl acetate, so that a large number of hydrophobic groups are introduced into the molecular chain of pea starch, the water resistance and thermal stability of pea starch are increased, so that the aerogel has more solid and dense pores, thereby improving the flame retardant and mechanical properties of the aerogel.
[0028] Preferably, the mass ratio of the pea starch to ethyl acetate is 1:(1.4-1.8).
[0029] By adopting the above technical solution and controlling the mass ratio of pea starch to ethyl acetate within the above range, the flame retardant properties and mechanical properties of the aerogel can be further improved.
[0030] In a second aspect, the present application provides a method for preparing an environmentally friendly aerogel as in the first aspect, which adopts the following technical solution: A method for preparing an environmentally friendly aerogel comprises the following steps: Pea starch and polyvinyl alcohol are added to deionized water, heated, and then glutaraldehyde is added and stirred evenly to form a mixed solution; the mixed solution is then poured into a mold while hot, cooled to room temperature to form a gel, and then subjected to a freeze-thaw cycle to obtain an aerogel.
[0031] In summary, the present application includes at least one of the following beneficial technical effects: 1. Pea starch and polyvinyl alcohol have the characteristics of good biodegradability. Therefore, the aerogel prepared with pea starch and polyvinyl alcohol as the main raw materials is easily degraded in the natural environment after being discarded, which effectively reduces the pollution to the environment; pea starch itself and pea starch and glutaraldehyde can be cross-linked to form a three-dimensional network structure; and pea starch and polyvinyl alcohol react to form hydrogen bonds, which increases the cross-linking density, thereby enhancing the density of the network structure, and then improving the flame retardant and mechanical properties of the aerogel.
[0032] 2. Under high temperature, the volatilization of water in the internal structure of attapulgite can effectively slow down the combustion reaction; at the same time, a large amount of magnesium and aluminum elements in the interior form a stable oxide layer at high temperature, thereby hindering the diffusion of flames and the transfer of heat, and having a good flame retardant effect. In addition, attapulgite is a fibrous structure. On the one hand, it can better support the carbon layer after the polymer is burned and carbonized, further improving the flame retardant effect. On the other hand, the fibrous structure gives attapulgite an excellent aspect ratio. Therefore, when attapulgite is wrapped in aerogel, it can form a more solid and dense skeleton structure, further improving the mechanical properties of aerogel. DETAILED DESCRIPTION
[0033] The present application discloses an environmentally friendly aerogel and a preparation method thereof, which is further described in detail below in conjunction with examples and comparative examples. The raw materials involved in the present application can all be obtained commercially, wherein polyvinyl alcohol is purchased from Aladdin Biochemical Technology Co., Ltd.
[0034] Example 1 The environmentally friendly aerogel includes the following raw materials by weight: 100 g of pea starch, 22 g of polyvinyl alcohol, and 2 g of glutaraldehyde.
[0035] The method for preparing the environmentally friendly aerogel comprises the following steps: Pea starch and polyvinyl alcohol were added to 500 g of deionized water, heated at 90 ° C for 1 hour, and then glutaraldehyde was added and stirred evenly to form a mixed solution; the mixed solution was poured into a mold while hot, cooled to 25 ° C to form a gel, and then three freeze-thaw cycles were performed, each freezing for 8 hours and thawing for 3 hours to obtain an aerogel.
[0036] Example 2 The environmentally friendly aerogel includes the following raw materials by weight: 120 g of pea starch, 28 g of polyvinyl alcohol, and 4 g of glutaraldehyde.
[0037] The method for preparing the environmentally friendly aerogel comprises the following steps: Pea starch and polyvinyl alcohol were added to 500 g of deionized water, heated at 90 ° C for 1 hour, and then glutaraldehyde was added and stirred evenly to form a mixed solution; the mixed solution was poured into a mold while hot, cooled to 25 ° C to form a gel, and then three freeze-thaw cycles were performed, each freezing for 8 hours and thawing for 3 hours to obtain an aerogel.
[0038] Example 3 The environmentally friendly aerogel includes the following raw materials by weight: 100 g of pea starch, 25 g of polyvinyl alcohol, and 3 g of glutaraldehyde.
[0039] The method for preparing the environmentally friendly aerogel comprises the following steps: Pea starch and polyvinyl alcohol were added to 500 g of deionized water, heated at 90 ° C for 1 hour, and then glutaraldehyde was added and stirred evenly to form a mixed solution; the mixed solution was poured into a mold while hot, cooled to 25 ° C to form a gel, and then three freeze-thaw cycles were performed, each freezing for 8 hours and thawing for 3 hours to obtain an aerogel.
[0040] Example 4 The difference between Example 4 and Example 3 is that the aerogel further includes 8 g of a flame retardant, and the flame retardant includes attapulgite.
[0041] The preparation method of the environmentally friendly aerogel comprises the following steps: Pea starch, polyvinyl alcohol and flame retardant were added to 500g of deionized water, heated at 90°C for 1h, and then glutaraldehyde was added and stirred evenly to form a mixed solution; the mixed solution was poured into a mold while hot, cooled to 25°C to form a gel, and then three freeze-thaw cycles were performed, with each freezing for 8h and thawing for 3h to obtain an aerogel.
[0042] Example 5 The difference between Example 5 and Example 4 is that the flame retardant further includes a flame retardant stabilizer, and the mass ratio of attapulgite to the flame retardant stabilizer is 4:1.
[0043] The preparation method of the flame retardant stabilizer comprises the following steps: Add 50g of shell powder to 500g of deionized water, stir for 1h, and then place it in an ultrasonic oscillator for 30min to obtain a shell powder suspension. Then add phytic acid until no obvious bubbles are generated. After standing for 2h, filter and collect the upper suspension. After centrifuging the suspension, collect the lower precipitate. Then place the precipitate in a freeze dryer and freeze-dry it for 24h to obtain a flame retardant stabilizer.
[0044] The preparation method of the flame retardant comprises the following steps: The attapulgite and the flame retardant stabilizer are mixed and stirred evenly to prepare the flame retardant.
[0045] Example 6 The difference between Example 6 and Example 4 is that the aerogel further includes 7 g of flame retardant, and the flame retardant includes attapulgite and a flame retardant stabilizer, and the mass ratio of attapulgite to the flame retardant stabilizer is 3:1.
[0046] The preparation method of the flame retardant stabilizer comprises the following steps: Add 50g of shell powder to 500g of deionized water, stir for 1h, and then place it in an ultrasonic oscillator for 30min to obtain a shell powder suspension. Then add phytic acid until no obvious bubbles are generated. After standing for 2h, filter and collect the upper suspension. After centrifuging the suspension, collect the lower precipitate. Then place the precipitate in a freeze dryer and freeze-dry it for 24h to obtain a flame retardant stabilizer.
[0047] The preparation method of the flame retardant comprises the following steps: The attapulgite and the flame retardant stabilizer are mixed and stirred evenly to prepare the flame retardant.
[0048] Example 7 The difference between Example 7 and Example 4 is that the aerogel further includes 9 g of flame retardant, and the flame retardant includes attapulgite and a flame retardant stabilizer, and the mass ratio of attapulgite to the flame retardant stabilizer is 5:1.
[0049] The preparation method of the flame retardant stabilizer comprises the following steps: Add 50g of shell powder to 500g of deionized water, stir for 1h, and then place it in an ultrasonic oscillator for 30min to obtain a shell powder suspension. Then add phytic acid until no obvious bubbles are generated. After standing for 2h, filter and collect the upper suspension. After centrifuging the suspension, collect the lower precipitate. Then place the precipitate in a freeze dryer and freeze-dry it for 24h to obtain a flame retardant stabilizer.
[0050] The preparation method of the flame retardant comprises the following steps: The attapulgite and the flame retardant stabilizer are mixed and stirred evenly to prepare the flame retardant.
[0051] Example 8 The difference between Example 8 and Example 5 is that the mass ratio of attapulgite to the flame retardant stabilizer is 2:1.
[0052] Example 9 The difference between Example 9 and Example 5 is that the mass ratio of attapulgite to the flame retardant stabilizer is 6:1.
[0053] Example 10 The difference between Example 10 and Example 5 is that the environmentally friendly aerogel further includes 1 g of chitosan.
[0054] The method for preparing the environmentally friendly aerogel comprises the following steps: S1, adding chitosan to a mixed solution of 95g deionized water and 5g acetic acid, stirring evenly to prepare a chitosan solution; S2. Add pea starch, polyvinyl alcohol, flame retardant and chitosan solution to 300g deionized water, heat at 90°C for 1h, add glutaraldehyde and stir evenly to form a mixed solution; pour the mixed solution into a mold while hot, cool to 25°C to form a gel, and then perform three freeze-thaw cycles, freezing for 8h and thawing for 3h each time to obtain an aerogel.
[0055] Embodiment 11 The difference between Example 11 and Example 10 is that the environmentally friendly aerogel further includes 3g of chitosan.
[0056] Example 12 The difference between Example 12 and Example 11 is that the environmentally friendly aerogel further includes 2 g of chitosan.
[0057] Example 13 The difference between Example 13 and Example 12 is that the environmentally friendly aerogel also includes 3g of boric acid.
[0058] The method for preparing the environmentally friendly aerogel comprises the following steps: S1, adding chitosan to a mixed solution of 95g deionized water and 5g acetic acid, stirring evenly to prepare a chitosan solution; S2, adding pea starch, polyvinyl alcohol, flame retardant, chitosan solution to 300g deionized water, heating at 90°C for 1h, adding glutaraldehyde, stirring evenly to form a mixed solution; then pouring the mixed solution into a mold while hot, cooling to 25°C to form a gel, and then performing three freeze-thaw cycles, each freezing for 8h and thawing for 3h, to obtain primary aerogel; S3. Add boric acid to 100 g of deionized water to prepare a boric acid solution, then soak the primary aerogel in the boric acid solution for 2 hours. After soaking, rinse the surface with deionized water, and finally freeze it in a refrigerator at -18°C for 1 hour, and then freeze-dry it in a freeze dryer for 20 minutes to obtain an environmentally friendly aerogel.
[0059] Embodiment 14 The difference between Example 14 and Example 13 is that the environmentally friendly aerogel further includes 5g of boric acid.
[0060] Embodiment 15 The difference between Example 15 and Example 13 is that the environmentally friendly aerogel further includes 4 g of boric acid.
[0061] Example 16 The difference between Example 16 and Example 15 is that the starch is prepared by modification, and the modification preparation method of the starch comprises the following steps: 10 g of starch was ultrasonically dispersed in 14 g of ethyl acetate to obtain a starch suspension, and then 1 g of pyridine was added and ultrasonicated for 0.5 h. Then, 0.5 g of acryloyl chloride was added and stirred thoroughly. After reacting at room temperature for 0.5 h, excess ethanol was added to terminate the reaction. The mixture was allowed to stand and repeatedly washed by centrifugation with ethanol for 4 times. The product after centrifugation was placed in a forced air oven at 80°C and dried for 24 h to obtain modified starch.
[0062] Embodiment 17 The difference between Example 17 and Example 15 is that the starch is prepared by modification, and the modification preparation method of the starch comprises the following steps: 10 g of starch was ultrasonically dispersed in 18 g of ethyl acetate to obtain a starch suspension, and then 1 g of pyridine was added and ultrasonicated for 0.5 h. Then 0.5 g of acryloyl chloride was added and stirred thoroughly. After reacting at room temperature for 0.5 h, excess ethanol was added to terminate the reaction. The mixture was allowed to stand and repeatedly washed by centrifugation with ethanol for 4 times. The product after centrifugation was placed in a forced air oven at 80°C and dried for 24 h to obtain modified starch.
[0063] Embodiment 18 The difference between Example 18 and Example 15 is that the starch is prepared by modification, and the modification preparation method of the starch comprises the following steps: 10 g of starch was ultrasonically dispersed in 16 g of ethyl acetate to obtain a starch suspension, and then 1 g of pyridine was added and ultrasonicated for 0.5 h. Then 0.5 g of acryloyl chloride was added and stirred sufficiently. After reacting at room temperature for 0.5 h, excess ethanol was added to terminate the reaction. The mixture was allowed to stand and repeatedly washed by centrifugation with ethanol for 4 times. The product after centrifugation was placed in a forced air oven at 80°C and dried for 24 h to obtain modified starch.
[0064] Embodiment 19 The difference between Example 19 and Example 18 is that the mass ratio of starch to ethyl acetate is 1:1.2.
[0065] Embodiment 20 The difference between Example 20 and Example 18 is that the mass ratio of starch to ethyl acetate is 1:2.0.
[0066] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the environmentally friendly aerogel does not contain polyvinyl alcohol.
[0067] Performance testing: 1. Flame retardancy The aerogel was made into a 10*80 mm sheet, and the limiting oxygen index of the aerogel was tested using an HC-2 limiting oxygen index instrument with an ignition time of 10 s. The test results are recorded in Table 1.
[0068] 2. Mechanical properties The aerogel was cut into a cuboid with a length of 8 cm and a width of 1 cm, and its thickness was measured. Then, the aerogel was put into an electronic universal testing machine to determine its tensile properties. The measurement was performed three times, and the average value was taken. The test results are recorded in Table 1.
[0069] Table 1 Data analysis Specifically combining the test results of Example 4 and Examples 1-3, the flame retardancy and mechanical properties of Example 4 are better than those of Examples 1-3. The analysis is as follows: the difference between Example 4 and Examples 1-3 is that the aerogel raw material contains attapulgite. On the one hand, attapulgite will evaporate water at high temperature and also generate a stable oxide layer, thereby improving the flame retardant properties of the aerogel. On the other hand, attapulgite can make the aerogel form a more solid and dense skeleton structure, thereby improving the mechanical properties of the aerogel.
[0070] Specifically combining the test results of Examples 5-7 and Example 4, the flame retardancy and mechanical properties of Example 5-7 are better than those of Example 4. The analysis is as follows: the difference between Example 5-7 and Example 4 is that: in addition to attapulgite, the flame retardant also contains a flame retardant stabilizer made from phytic acid and shell powder as main raw materials. On the one hand, the flame retardant stabilizer can generate a phosphide layer and reduce the concentration of combustible gas in the gas phase, thereby improving the flame retardant properties of the aerogel. On the other hand, it reduces the addition of more attapulgite, which makes the aerogel deform and easily brittle and break, thereby improving the mechanical properties of the aerogel.
[0071] Specifically combining the test results of Examples 10-12 and Example 5, the flame retardancy and mechanical properties of Examples 10-12 are better than those of Example 5. The analysis is as follows: the difference between Examples 10-12 and Example 5 is that: chitosan is also included in the aerogel raw material. On the one hand, chitosan can produce non-flammable gas nitrogen, which plays a role in diluting oxygen, and can also form a complex layer with the flame retardant stabilizer, thereby improving the flame retardancy of the aerogel. On the other hand, glutaraldehyde can react with chitosan to strengthen the chemical cross-linking effect between the network skeletons, and the complex layer also improves the density of the surface layer of the aerogel, thereby improving the mechanical properties of the aerogel.
[0072] Specifically combining the test results of Examples 13-15 and Example 12, the flame retardancy and mechanical properties of Examples 13-15 are better than those of Example 12. The analysis is as follows: the difference between Examples 13-15 and Example 12 is that: boric acid is also contained in the aerogel raw material, which, on the one hand, enables the aerogel to form a multiple cross-linked structure, and forms a dense protective film on the surface of the aerogel, thereby improving the flame retardancy of the aerogel, and on the other hand, the multiple cross-linked structure can improve the mechanical properties of the aerogel.
[0073] Specifically combining the test results of Examples 16-18 and Example 15, the flame retardancy and mechanical properties of Examples 16-18 are better than those of Example 15. The analysis is as follows: the difference between Examples 16-18 and Example 15 is that after the pea starch is esterified with ethyl acetate, the aerogel has more solid and dense pores, thereby improving the flame retardancy and mechanical properties of the aerogel.
[0074] Specifically combining the test results of Example 1 and Comparative Example 1, the flame retardancy and mechanical properties of Example 1 are better than those of Comparative Example 1. The analysis is as follows: the difference between Example 1 and Comparative Example 1 is that the raw material contains polyvinyl alcohol, which enhances the density of the network structure, thereby improving the flame retardancy and mechanical properties.
[0075] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. An environmentally friendly aerogel, characterized in that: The invention comprises the following raw materials in parts by weight: 100-120 parts of pea starch, 22-28 parts of polyvinyl alcohol and 2-4 parts of pentanediol.
2. The environmentally friendly aerogel according to claim 1, characterized in that: The raw materials also include 7-9 parts of flame retardant, and the flame retardant includes attapulgite.
3. The environmentally friendly aerogel according to claim 2, characterized in that: The flame retardant also includes a flame retardant stabilizer; The preparation method of the flame retardant stabilizer comprises the following steps: The shell powder is added to deionized water, stirred evenly to obtain a shell powder suspension, phytic acid is added, the upper suspension is collected by filtering after standing, the suspension is centrifuged and the lower precipitate is collected, and the precipitate is freeze-dried to obtain a flame retardant stabilizer; The method for preparing the flame retardant comprises the following steps: The attapulgite and the flame retardant stabilizer are mixed and stirred evenly to prepare the flame retardant.
4. The environmentally friendly aerogel according to claim 3, characterized in that: The mass ratio of the attapulgite to the flame retardant stabilizer is (3-5):
1.
5. The environmentally friendly aerogel according to claim 3, characterized in that: The raw materials also include 1-3 parts of chitosan.
6. The environmentally friendly aerogel according to claim 3, characterized in that: The raw materials also include 3-5 parts of boric acid.
7. The environmentally friendly aerogel according to claim 1, characterized in that: The pea starch is prepared by modification, and the modification preparation method of the pea starch comprises the following steps: Pea starch is added to ethyl acetate and stirred evenly to obtain a starch suspension, and then pyridine is added and stirred evenly. Acryloyl chloride is added and stirred sufficiently. After the reaction at room temperature, excess ethanol is added to terminate the reaction. The reaction is then allowed to stand, washed and dried in sequence to obtain a modified starch.
8. The environmentally friendly aerogel according to claim 7, characterized in that: The mass ratio of the pea starch to ethyl acetate is 1:(1.4-1.8).
9. A method for preparing the environmentally friendly aerogel according to claim 1, characterized in that: The steps include: Pea starch and polyvinyl alcohol are added to deionized water, heated, and then pentanediol is added and stirred evenly to form a mixed liquid; the mixed liquid is then poured into a mold while hot, cooled to room temperature to form a gel, and then subjected to a freeze-thaw cycle to obtain an aerogel.